Pengaruh Konsentrasi Ekstrak Nanas (Ananas Comosus) Dan Waktu Fermentasi Pada Pembuatan Nata De Coco Dari Limbah Air Kelapa - Mulia Aria Suzanni; Aris Munandar; Saudah Saudah (Fakultas Teknik, 2020)
Coconut water waste discharged into the environment is one of the problems in traditional markets. Coconut water waste treatment can be done simply by making nata de coco using the starter of bacteria Acetobacter xylinum obtained from pineapple extracts. The research is aimed to study the effect of the concentration of pineapple extract (Ananas comosus) and fermentation time in making nata de coco from coconut water waste by experimental methods. The results of nata de coco can be seen from the maximum thickness level obtained by 1.4 cm at a starter concentration of 150 ml, 200 ml, and 250 ml with a fermentation time of 21 days. The best quality of nata de coco is at 200 ml and 250 ml starter concentrations witch a content water of 13.79% and mineral content of 0.175%. The high percentage of nata de coco favorite level is the 250 ml starter concentration, based on the level of preference for color, shape, aroma, taste, and suppleness.